2017
DOI: 10.15549/jeecar.v4i2.180
|View full text |Cite
|
Sign up to set email alerts
|

How to Publish in Academic Journals: Writing a Strong and Organized Introduction Section

Abstract: Publishing in quality academic journals is challenging. Authors who want to improve their chances of publishing in management and allied business and social science journals can save themselves much time and frustration by ensuring that manuscripts are consistent with the journal's aims and scope and what the field requires in terms of addressing unanswered research questions or improvements to current theory and evidence. It is well-understood if a manuscript lacks theoretical grounding or makes significant m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…As our study focuses on nascent businesses in China, we also hope to shed light on the questions surrounding firms in the Chinese context (Ahlstrom, Chen, & Yeh, 2010;Tang, 2010). Following Ahlstrom (2015Ahlstrom ( , 2017, we have tried to use this introduction to make clear our research question and focus: Does being a born-global make a startup more or less likely to quit before launch, and how do innovativeness and information diversity affect the decision to start or stop a born-global venture? Thus, we will look at born-globals and non-born-globals in studying what makes nascent entrepreneurs choose the born-global path, and then we will focus on the born-globals in addressing how innovativeness and information diversity affect the decision to quit (or not quit) a nascent born-global.…”
mentioning
confidence: 99%
“…As our study focuses on nascent businesses in China, we also hope to shed light on the questions surrounding firms in the Chinese context (Ahlstrom, Chen, & Yeh, 2010;Tang, 2010). Following Ahlstrom (2015Ahlstrom ( , 2017, we have tried to use this introduction to make clear our research question and focus: Does being a born-global make a startup more or less likely to quit before launch, and how do innovativeness and information diversity affect the decision to start or stop a born-global venture? Thus, we will look at born-globals and non-born-globals in studying what makes nascent entrepreneurs choose the born-global path, and then we will focus on the born-globals in addressing how innovativeness and information diversity affect the decision to quit (or not quit) a nascent born-global.…”
mentioning
confidence: 99%
“…These novice writers are being oriented in the academic discourse community to learn the common and best practices. Ahlstrom (2017) claims that writers who fail to present interesting and specific focus of research introductions do not meet the demands of editors and reviewers. Therefore, exposing students to various strategies is useful.…”
Section: Resultsmentioning
confidence: 99%
“…Swales and Feak (2012) indicate that studies that address new and relevant problems are cited more because of their potential contribution to scholarship. Editors and reviewers may find reasons to reject a RA if the introduction does not specifically indicate the purpose and the contribution it will make to the area of a field (Ahlstrom, 2017). Consequently, novice writers require the knowledge of best practices in problematising their problem in a RA, because the introduction section of research work poses serious challenges to writers (Afful, 2008;Bhatia, 1993;Suryani et al, 2015;Swales, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…The Introduction section also conceptualizes the overall research, usually with less information on the research results. Ahlstrom (2017) characterized it as a microcosm of the whole research paper. Flowerdew (1999) indicated that the Introduction section is one of the most difficult sections to write in a research paper because the author needs to convince the readers "of the importance of their research and the arguments they are putting forward.…”
Section: Introductionmentioning
confidence: 99%